2017
DOI: 10.1177/0886260517701454
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Disparities in Trauma-Related Mental Illness: Is Ethnic Identity a Buffer?

Abstract: Despite evidence that racial and ethnic characteristics influence the impact of traumatic exposure on psychological health, little is known about how race and ethnic identity can alter, and possibly protect against, the effects of trauma on the psychiatric diagnoses of women. Therefore, the present study examined the moderating role of race/ethnicity and ethnic identity in the link between trauma exposure and psychiatric diagnosis for African American and Caucasian college women. Participants were a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Table 1 describes characteristics of women included in the present study, overall and by site. The median age was 46 years (interquartile range (IQR) = [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]), and the majority (63%) had at least a high school education.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 describes characteristics of women included in the present study, overall and by site. The median age was 46 years (interquartile range (IQR) = [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]), and the majority (63%) had at least a high school education.…”
Section: Resultsmentioning
confidence: 99%
“…[47][48][49] Specifically, research indicates that this strong sense of ethnic identity may serve to promote resilience in situations of stigma and discrimination. 50,51 Among African Americans, greater ethnic identity is associated with lower anxiety, depression and psychological stress and greater coping, optimism and self-esteem. 31,52,53 Moreover, among a sample of young African-American women, stronger ethnic identity wasassociated with less HIV-related risk-taking, 54 and in a sample of (predominately African-American) women living with HIV, greater ethnic identity was associated with less perceived stress.…”
Section: Introductionmentioning
confidence: 99%
“…Based on indings from young adult studies that have utilized more stringent tests of invariance, there is evidence to suggest comparisons across ethnic groups based on MEIM scores may not be valid (Yap et al, 2014(Yap et al, , 2016. Such indings call into question the validity of the wide-spread use of the MEIM to compare ethnic groups (Carter et al, 2018;Dandy et al, 2008;Gummadam et al, 2016;Rahim-Williams et al, 2007;Townsend et al, 2020), and provide the impetus to further examine the measurement structure and invariance in an adolescent population. The identiication of the measurement invariance of the MEIM across ethnic groups and developmental periods is critical to ensure the appropriate use of the measure as well as the validity of the results of studies that use the measure in this way.…”
Section: Present Studymentioning
confidence: 99%
“…Cultural beliefs and values have been found to influence the way an individual understands and gives meaning to a traumatic event (Townsend, Kaltman, Saleem, Coker-Appiah, & Green, 2017). Pérez Benítez and colleagues (2010) suggested that social stigma and perception of traumatic events based on one's cultural background may play a role in understanding the consequences of This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Ethnic Pride and Trauma Copingmentioning
confidence: 99%